Simulación de un derrame de hidrocarburos en el puerto pesquero de santa rosa del cantón salinas - Marín Jarrín, María José (2010)
The port of Santa Rosa, province of Santa Elena, presents a community dedicated to the artisanal fishery, which demands the manipulation of gasoline in ships and coastal dispatchers. Hence, it is necessary to predict the effects of a spill in this area. A confrontation matrix allowed comparing the most common oil-spill simulation programs and the most important characteristics in order to adjust to the study area. Two models were chosen: ADIOS2 and GNOME, which allow the simulation of oil aging in the ocean and the spill trajectory, respectively. Using these programs, six Unleaded Gasoline spills were simulated in two zones: the fishermen’s dockage area and, the gasoline-supplying dock in the San Jacinto Point. Data of the two climatic stations of the region were used: rainy and dry season, with variable parameters of temperature and wind. It was observed that in dry season, most of the spilled oil is evaporated and dispersed in less than 6 hours, and no barrel reaches land. However, in rainy season, all the spills reach land since the first hour after the spill.